PRINCIPLES FOR MARKET ORIENTATION - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
The goal of market orientation is to improve rural incomes and the quality of rural life. Market orientation relates not only to farmers but to all sections of the chain involved in food and agro-industry including the important services sector....